Faktor-Faktor yang Berhubungan dengan Kepatuhan Wanita Usia Subur dalam Keikutsertaan Pemeriksaan IVA di Wilayah Kerja UPT Puskesmas Pemulutan Tahun 2025 - Defitri Dawazad; Intan Sari; Wahyu Ernawati; Merisa Riski (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Cervical cancer rates remain high both globally and in Indonesia. The incidence rate of cervical cancer is 13.62 cases per 100,000 population. The Indonesian government has launched a national program to prevent and detect cervical cancer early through the IVA program. This study aims to determine the relationship between knowledge, attitude, and spousal support with IVA screening at the Pemulutan Community Health Center. This study used a quantitative analytical survey design with a cross-sectional approach. The study was conducted at the Pemulutan Community Health Center on June 2025, with a population of 4,855 people and a sample of 98 women of childbearing age (30-50 years) who were interviewed directly using a questionnaire. The sampling technique used accidental sampling. The results of the chi-square test obtained a P-value (0.002) < α (0.05), which means that there is a significant relationship between attitude and IVA screening. The chi-square test results obtained a P-value (0.001) < α (0.05), which means that there is a significant relationship between husband support and IVA screening. There is a relationship between knowledge, attitude, husband support, and IVA screening in the working area of the Pemulutan Community Health Center. Recommendations for health workers to increase awareness of early cervical cancer screening to improve IVA coverage.